Mechanism of low molecular weight GTP binding protein RAC1 in injury of neural function of rats with cerebral ischemia reperfusion - Li, Ya-Hong; Qiao, Lu-Jun; Lin, Xiao-Ying (Asian Pacific journal of tropical medicine, 2016)
Objective: To discuss the mechanism of low molecular weight GTP binding protein RAC1 in the injury of neural function based on building the rat model of cerebral ischemia reperfusion. Methods: Middle cerebral artery of rats was ligated and the ligature was released to restore the perfusion after 2 h, the rat model of cerebral ischemia reperfusion injury was built, while the middle cerebral artery was ligated. The rats were randomly divided into the sham group, cerebral ischemia reperfusion group(I/R group) and the group with the injection of RAC1 activity inhibitor NSC23766(NSC group). The survival and neurological severity score of rats in each group were observed and recorded. Nissl staining was employed to observe the nerve cells, and Western blot to detect expression of RAC1, superoxide dismutase and malondialdehyde. Results: Number of nerve cells for rats in NSC group was significantly more than that in I/R group, but significantly less than that in sham group, with the statistical difference(P<0.05). The brain water content for rats in NSC group was significantly lower than that in I/R group, but significantly higher than that in sham group, with the statistical difference(P<0.05). The expression of RAC1 and malondialdehyde for rats in NSC group was significantly lower than that in I/R group, but higher than that in sham group; while the expression of superoxide dismutase was lower than that in sham group, but higher than that in I/R group, with the statistical difference(P<0.05). Conclusions: The inhibition of RAC1 activity can reduce the oxidative stress, reduce the neurologic impairment because of cerebral ischemia reperfusion and thus protect the neural function.